Conceptual Model of Child Worksheets (LKA) Based on a Scientific Approach Incorporating Religious Moderation - Mashlahah, Any Umy; Bakir, Edi Bahtiar (Jurusan PIAUD UIN Siber Syekh Nurjati Cirebon, 2025)
Religious moderation is a fundamental value that needs to be internalized from early childhood to foster tolerant, fair, and inclusive character development. However, the implementation of religious moderation in early childhood education, particularly in Raudhatul Athfal (Islamic early childhood institutions), remains largely normative and is rarely supported by operational and systematic instructional tools. This study aims to develop a scientific approach–based children’s worksheet (Lembar Kerja Anak/LKA) model as a medium for internalizing religious moderation values in Raudhatul Athfal.This research employed a Research and Development (R&D) design, encompassing needs analysis, product design, development, expert validation, limited field testing, and product revision. The research subjects involved early childhood education experts, instructional design experts, religious moderation experts, and Raudhatul Athfal teachers as users. Data were collected through validation questionnaires, practicality questionnaires, and classroom observations, and were analyzed using descriptive quantitative and qualitative techniques.The results indicate that the developed scientific approach–based LKA is categorized as highly valid in terms of content relevance, instructional design, and religious moderation integration, and highly practical for classroom implementation. The use of the LKA effectively facilitated the internalization of religious moderation values, including tolerance, cooperation, fairness, and respect for diversity, through child-centered learning activities and structured social interaction. These findings demonstrate that the scientific approach is not only effective in enhancing children’s cognitive development but also serves as a powerful pedagogical vehicle for character and religious value internalization when systematically embedded in instructional materials.This study contributes to early childhood education research by offering an applicable and context-sensitive scientific worksheet model that supports the strengthening of religious moderation education in Islamic early childhood settings.